2020
DOI: 10.2147/jir.s278911
|View full text |Cite
|
Sign up to set email alerts
|

<p>HPV-16 E2/E6 and POU5F1B as Biomarkers to Determine Cervical High-Grade Squamous Lesions and More</p>

Abstract: Purpose Human papillomavirus-16 (HPV-16) is the most carcinogenic HPV genotype. This study aimed to evaluate the clinical value of POU5F1B and HPV-16-E2/E6 by cervical cytology specimens to predict the cervical intraepithelial neoplasia two grade and more (CIN2+). Methods Finally, 248 patients with HPV-16 single infection were enrolled. Using cytology specimen by real-time quantitative PCR (qPCR), POU5F1B mRNA and HPV-16-E2/E6 were detected. The relationship of POU5F1B,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Third, blocking the trans -acting mediators released by POU5F1B-expressing cells could also be of benefit, as these molecules are predicted to increase the oncogenic properties of neighboring cells and of the tumor microenvironment. Finally, the presence of POU5F1B -encoding TcGTs in several other malignancies, including breast, prostate, stomach, and uterus, the previous identification of the POU5F1B locus as an integration hotspot for human papillomavirus and the coincidence of its transcripts with more advanced histological grades in cervical cancer 59 , 60 , as well as the documentation of its amplification in some gastric tumors 51 and growth-promoting effect on hepatocellular carcinoma cell lines 50 all indicate that our findings have a relevance that likely extends well beyond colorectal cancer alone.…”
Section: Discussionmentioning
confidence: 98%
“…Third, blocking the trans -acting mediators released by POU5F1B-expressing cells could also be of benefit, as these molecules are predicted to increase the oncogenic properties of neighboring cells and of the tumor microenvironment. Finally, the presence of POU5F1B -encoding TcGTs in several other malignancies, including breast, prostate, stomach, and uterus, the previous identification of the POU5F1B locus as an integration hotspot for human papillomavirus and the coincidence of its transcripts with more advanced histological grades in cervical cancer 59 , 60 , as well as the documentation of its amplification in some gastric tumors 51 and growth-promoting effect on hepatocellular carcinoma cell lines 50 all indicate that our findings have a relevance that likely extends well beyond colorectal cancer alone.…”
Section: Discussionmentioning
confidence: 98%
“…The receiver operating characteristic (ROC) curve analysis was further performed to assess the diagnostic performance of the identified potential biomarkers. [30][31][32][33] The area under the curve (AUC) was the evaluation index. In general, an AUC of 0.5 to 07, 0.7 to 0.8, 0.8 to 0.9 and 0.9 to 1.0 were considered no discrimination, acceptable, excellent, and outstanding, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Another study revealed that the expression of C-myc and POU5F1B is higher in CIN grade 2 or worse (CIN2+) than in normal patients or CIN1. 21,22 hTERT expression also increases in CIN2+. 23 Although these findings suggest that BV may play an important role in the progression of HR-HPV infection to cervical cancer, the relationship between cervicovaginal microbiota and persistent HR-…”
Section: Introductionmentioning
confidence: 93%
“…Altoos et al 20 demonstrated that the expression level of NF‐κBp65 is associated with poor clinical outcomes in patients with locally advanced cervical cancer. Another study revealed that the expression of C‐myc and POU5F1B is higher in CIN grade 2 or worse (CIN2+) than in normal patients or CIN1 21,22 . hTERT expression also increases in CIN2+ 23 …”
Section: Introductionmentioning
confidence: 99%